Cybersecurity in ERP-Integrated Supply Chains: Risks and Mitigation Strategies - Ravindra Khokrale (Eastasouth Institute, 2025)
Cybersecurity risks have emerged as a burning issue as global supply chains increasingly use Enterprise Resource Planning (ERP) systems to integrate official systems into their supply chains. ERP systems unite different stakeholders, including suppliers, logistics, and finance teams, making it possible to exchange real-time information and streamline it. However, there is a possibility of cyberattacks in these systems, particularly when integrating with third-party systems, having poor access control, and using outdated software. The emergence of high-profile attacks such as the 2017 NotPetya has underscored the dramatic financial and operational loss factors because of ERP breaches and outlined the importance of firm protection against cyberattacks. This paper discusses the most significant cybersecurity threats to ERP-integrated supply chains and voices the successful mitigation measures. Major risks observed are the vulnerability of third parties, weak access control, and the use of old ERP systems. Such measures as multi-factor authentication, continuous monitoring, and vendor risk management are also evaluated as the best practices of the study. The study provides effective suggestions that can be implemented in organizations to ensure that their ERP-based supply chains are secured, and the chances of data breaches and disruptions in operations are reduced. With the digitalization of supply chains, the future is seen to utilize the new capabilities to use new technologies, including artificial intelligence and blockchain, to further improve the security and information integrity of ERP.